EFFECT OF DIETARY SUPPLEMENTATION OF LECITHIN ON SERUM LIPID PROFILE OF LARGE WHITE YORKSHIRE PIGS FED HIGH FAT DIET - Arathy Saseendran; K. Ally (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The experiment was conducted to assess the effect of dietary supplementation of lecithin on serum lipid profile of pigs fed high fat diet. Thirty two weaned Large White Yorkshire piglets were randomly divided into three groups and allotted to three dietary treatments, T1 (control ration as per NRC, 1998), T2 (control ration plus 5 per cent animal fat) and T3 (T2 plus 0.5 per cent lecithin). Blood samples were collected for lipid profile estimation. The serum triglycerides, total cholesterol, HDL, LDL cholesterol, LDL: HDL ratio and total cholesterol: HDL ratio of pigs maintained on three dietary treatments ranged from 36.62 to 46.12 mg/dl, 74.56 to 101.10 mg/dl, 35.30 to 47.77 mg/dl, 31.94 to 44.10 mg/dl, 0.89 to 1.08 and 2.11 to 2.16, respectively. The animals in T2 had higher (p<0.01) level of all serum lipid parameters observed in the study except HDL cholesterol where it shows similar effect with T3. The control group (T1) shows lower value of all lipid parameters studied. Elevated serum lipid profile observed for fat added group can be significantly reduced by dietary incorporation of lecithin along with fat in pigs.